2021
DOI: 10.1038/s41598-021-82566-w
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus is common in patients with chronic liver disease and is improved by nalfurafine hydrochloride

Abstract: Pruritus is known to be a common complication in hepatitis patients, but the exact frequency and degree are not fully elucidated. Thus, we evaluated pruritus of 450 patients with chronic liver disease at our hospital. Pruritus was observed in 240 (53%) of the patients. Pruritus was significantly associated with males (OR = 1.51, P = 0.038) and patients with alkaline phosphatase (ALP) ≥ 200 U/L (OR = 1.56, P = 0.0495) and was significantly less in HBsAg-positive patients (OR = 0.449, P = 0.004). Seasonally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Previous studies mainly reported the prevalence of pruritus in patients with chronic liver disease and the effect of nalfurafine hydrochloride and the treatment response rates in those with pruritus [6,8] . However, factors influencing the treatment response have not been evaluated and thus remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly reported the prevalence of pruritus in patients with chronic liver disease and the effect of nalfurafine hydrochloride and the treatment response rates in those with pruritus [6,8] . However, factors influencing the treatment response have not been evaluated and thus remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of κ-opioid receptor agonists, such as nalfurafine hydrochloride, is crucial for prevailing over the pruritus-inducing μ-opioid system. Previous studies mainly reported the prevalence of pruritus in patients with chronic liver disease and the effect of nalfurafine hydrochloride and the treatment response rates in those with pruritus 6 , 8 . However, factors influencing the treatment response have not been evaluated and thus remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This randomized trial demonstrated the efficacy of nalfurafine hydrochloride 2.5 or 5 μg daily for 12 weeks using a visual analogue scale (VAS) and the pruritus score. Another clinical study showed that the response rate to nalfurafine hydrochloride was 71% in 24 refractory pruritus patients 8 . However, these studies excluded patients with severe liver cirrhosis (i.e., Child–Pugh class C) from the subjects, who may have more frequent or more severe pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, placebo-controlled trial including a rather inhomogeneous group of 318 patients with different liver diseases, treatment with nalfurafine resulted in a statistically significant but clinically questionable reduction of pruritus (16). This trial and other studies on hepatic pruritus (19,34) included patients suffering from very diverse underlying liver diseases, ranging from chronic viral hepatitis, immunemediated cholestatic disorders including overlap syndromes, to liver cirrhosis of various causes. The selection and examination of these inhomogeneous patient collectives might have resulted in divergent laboratory findings and reactions to treatment, which we hoped to minimize here by choosing well-defined patient and control groups.…”
Section: Discussionmentioning
confidence: 99%